Targeting and scaling up of Agricultural Water Management interventions in the White Volta Basin, Ghana. - Granaham, Patricia (CGIAR Challenge Program on Water and Food, 2012)
Key  findings: • From   the   PGIS   survey,   six   of   the   interventions   (two   small   reservoirs,   earth   bunds,   stone  bunds,  treadle  pump,  water  pumps  and  shallow  wells)  were  identified  with  the   help  of  key  stakeholders  to  the  study. • Increment   of   farmers’   income-‐   Education   of   their   children,   NHIS,   roofing   sheet   for   their   building   and   reinvest   in   next   season.   Increase   yield   (e.g.   to   about   300%   of   rice   at  Beo),  increase  in  crop  diversity  and  raising  of  seedling • With   the   exception   of   treadle   pump   usage   which   remains   the   same,   the   number   of   farmers  adopting  the  interventions  has  increased  spontaneously. o The  high  adoption  of  shallow  well  at  Doba  was  due  to  its  indigenous  nature,   increase   population,   migration   of   some   Burkinabe   into   the   area   and   the   high   water  table  during  the  early  dry  seasons. o The  reason  for  stone  and  earth  bunds  adoptions  increment  is  mainly  due  to   the  availability  of  the  construction  material  and  the  apparent  improvement  in   livelihoods  of  those  who  started  first. o The adoption of the motorized pumps in Pwalugu has also increased from 2007 to 2011. However, due to the cost of pump, 3 women out of the 143 farmers are using pumps. • Farmers  and  stakeholders  consulted  claimed  apart  from  Involvement  of  communities   in  project,  water  availability,  training  on  farm  management  and  accessibility  market,   other  input  like  fertilizer  has  contributed  to  the  success  of  the  interventions • The   developed   suitability   maps   indicated   that   optimally/highly   suitable   areas   for   small  reservoirs,  stone  bunds  and  earth  bunds  are  located  in  the  eastern  part  of  UER   as  5766km2  (66%),  4410km2  (50%)  and  6071km2  (69%)  of  the  total  area  respectively.